Mechanical, dielectric, and hydrophobicity behavior of coconut shell biochar toughened Caryota urens natural fiber reinforced epoxy composite - Jayabalakrishnan, D; Prabhu, P; Mohamed, Iqbal S; Mugendiran, V; Ravi, S; Arun Prakash V R (Polymer composites, 2022)
High toughness epoxy bio‐composites were prepared using Caryota urens fiber and biochar particle for light weight and low cost engineering applications. The main aim of this research was to study the effect of adding biochar along with C. urens fiber in epoxy resin composite and its properties. The biochar used in this present study was prepared from coconut shell using pyrolysis process. The composites prepared with 5 vol% of biochar gives highest tensile strength and modulus of 172 MPa and 6.7 GPa. Similarly, the biochar of 7 vol% in epoxy resin reduced the wear volume to the greater extend. Moreover, a highest dielectric constant and loss factor of 6.2, 1.6, and a thermal conductivity of 0.33 W/mK with high hydrophobic contact angle of 70° was observed for composite made using 7 vol% of biochar. These improved dielectric, mechanical, barrier and tribological properties composite could be used as microwave shielding material in electronic gadgets, signal processing units and other telecommunication devices as shielding material with good mechanical properties required. Stages in biochar production.